A Study on Human Foot Pressure Behaviour and Balancing Characteristics. Issue 1 (July 2020) - Asmi, A N; Othman, N; Zain, M Z Md; Wahid, M Ab
Abstract: This paper presents an experimental investigation on pressure distribution on human foot and balancing characteristics on human foot health. Feet are the parts of the human body that will sustain the highest pressure during standing. Analysis of foot plantar pressure distributions helps in revealing the interface pressure between the foot plantar surface and the shoe sole. The objectives of this research are to study on behavioural of the human foot pressure distribution and balancing during standing. In this study, five factors are considered for the experiment to establish the behavioural of humans' foot, which are body mass index, gender, type of arch, diabetic and progressive foot deformity. Therefore, the experiment is conducted in order to know the pressure distribution based on factors by using Force Resistive Sensor. As a result, foot pressure distribution for normal subjects usually concentrated on the forefoot, followed by hind foot and middle foot. Body mass index also affects the pressure distribution as an increase in pressure follows an increase in body mass index and vice versa. As for gender factor, there is no significant difference in the pattern of pressure distribution between males and females. While for the type of feet arch factor, the different arch will give different locations of peak pressure. The diabetic factor, pressures will distribute more to the metatarsals and heel area while for progressive foot deformity factor, the pressure is usually distributed at the metatarsals and the toe area.